ANALISIS KARAKTERISTIK RESPONDEN DALAM MENGGALI PENGEMBANGAN PARENTS ASISSTED LEARNING MODEL (PALM) TERHADAP KEMAMPUAN LITERASI PESERTA DIDIK - Budiarti, Erika Mei; Kusumaningrum, Desi Eri; Gunawan, Imam; Sumarsono, Raden Bambang; Aziz, Abdullah Aminuddin; Burham, Akbar Syach Ichwanda; Bengen, Evanly Jorji (Managere: Indonesian Journal of Educational Management, 2022)
This study aimed to describe the characteristics of the selected respondents in exploring the development of the Parents Assisted Learning Model (PALM) on the literacy skills of upper-class students in public elementary schools in coastal and mountainous areas. The data analysis technique used is the descriptive analysis technique. The selected research sample is the parents of students as the key subjects of PALM implementation. The results showed that the characteristics of the parents of students who support the development of the Parents Assisted Learning Model (PALM) in order to support the literacy movement of students in elementary schools in coastal and mountainous areas are the parents of students with the type of work of farmer/fisherman/trader/honorary.